Exploring the relationship between Islamic personality and parenting style - Nooraini Othman; Salasiah Khairollah (Universiti Kebangsaan Malaysia, 2013)
This study was conducted to identify the parenting styles which influence the Islamic personality among students from one of the secondary school in Batu Pahat district, Johor. Using strata random sampling technique, a total of 302 students from form 1 to form 6 of the secondary school was chosen as the respondents. This correlational study used questionnaire as an instrument for its data collection. The data analysis was done using the descriptive and inferential statistical analysis with the help of Statistical Packages for Social Sciences (SPSS) version 17.0. Descriptive analysis result shows a medium level of authoritative parenting style, high level of authoritarian parenting style and low level of permissive parenting style were practiced. Inferential analysis result shows the existence of a significant relationship between parenting styles (authoritarian, authoritative and permissive) and Islamic personality.